Chemical composition and biological activities of Heterotrigona Itama and Geniotrigona Thoracica propolis from Malaysia - Nurhamizah Ibrahim
The chemical composition of propolis is highly variable and complex depends on the bee species at the sampling location. However, data on comparison of chemical properties between Malaysian stingless bee species was not found at the time of this research. It is crucial to compare the differences of the quality of propolis from different species through the examination on physicochemical characteristics, biological activity and chemical composition before developing propolis as a therapeutic agent or value-added products. This study was performed to evaluate and compare the nutritional value, chemical composition and biological activity of Malaysian stingless bee propolis of two species, Heterotrigona itarna (HI) and Geniotrigona thoracica (GT). The nutritional value, the content of moisture, ash, crude protein, fat, fibre and carbohydrate was determined. The spectroscopic technique namely Fourier Transform Infrared (FTIR) and chromatographic techniques, which were High Performance Thin Layer Chromatography (HPTLC) and Gas Chromatography-Mass Spectrometry (GC-MS) were used to establish chemical profile. FTIR and HPTLC data were subjected to chemometrics analysis such as Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) to evaluate the discrimination between samples. Proximate value analysis showed HI had more moisture content, crude protein and carbohydrate compared to that of GT. On the other hand, GT contained more fibre compared to HI. Propolis from HI also had a higher content of total flavonoid and phenolic compounds. The chemical profile of propolis showed a clear separation between samples in different species. Principal component analysis of HPTLC showed HI propolis were differ from GT propolis with their PC 1 and PC2 values of 51.26% and 46.74%, respectively at 254 nm. While at 366 nm, their PCl and PC2 values of 47.84% and 44.68%, respectively. HPTLC confirmed the two clusters established from HCA grouping of HI and GT propolis for both extracts. PCA of FTIR showed that ethanol extract for both species clustered quite similarly but in methanol extract were clustered apart from each other with their PC 1 and PC2 values of 54.01 % and 41.61 %. However, HCA grouping of FTIR were confirmed that two clusters were established of HI and GT propolis for both extracts. In biological analysis, HI propolis exhibited stronger antioxidant activity through DPPH free radical scavenging activity for methanol and ethanol extract with their ICso values of 10 ug/ml, dan 20 ug/ml, compared to GT propolis for methanol and ethanol extract with their ICso values of 270 ug/rnl. dan 400 ug/ml., HI also exhibited stronger antibacterial activity compared to GT extracts. In conclusion, data gathered in this study revealed that bee species play a role in collecting propolis as shown by nutritional, chemical and biological profile of propolis and should put into account in decision of further development for propolis.